k-space function spaces - R. A. McCoy (International Journal of Mathematics and Mathematical Sciences)
A study is made of the properties on X which characterize when Cπ(X) is a k-space, where Cπ(X) is the space of real-valued continuous functions on X having the topology of pointwise convergence. Other properties related to the k-space property are also considered.